The Effect of Work Environment, Work Discipline on Employee Performance with Communication as an Intermediate Variable in Government Agencies - Muhammad Fajri; Maulana, Frans; Azhari, Ibel (Yayasan Gema Bina Nusantara, 2023)
The population in this research is all employees, so the total population for this research is 129 people. The sample in this study was 129 employees. This research uses census sampling techniques. In preparing this research, data collection techniques were obtained, including interviews and questionnaires. The test results show that the relationship between the work environment and communication is negative and not significant. Thus, it can be said that the work environment hypothesis has a negative influence on communication and is not significant or rejected. There is a relationship between work discipline and communication that is both negative and significant. Thus, it can be said that the hypothesis that work discipline has a negative and significant influence on motivation is accepted. There is a relationship between communication and performance that is positive and significant. Thus, it can be said that the hypothesis that communication has a positive and significant influence on performance is accepted. There is a relationship between work environment and performance that is positive but not significant. Thus, it can be said that the hypothesis that the work environment has a positive and significant influence on performance is accepted. A good work environment encourages employee morale, which can improve employee performance. There is a relationship between work discipline and performance that is positive and significant. Thus, it can be said that the hypothesis that work discipline has a positive and significant influence on performance is accepted.